Particípios parasíticos em português? O caso do gerúndio composto - López, Vanessa (Revista da Associação Portuguesa de Linguística, 2019)
The compound gerund (gerund of the auxiliary + past participle) in Romance languages typically expresses an anteriority relation between the situation described by the (adjunct) gerund clause and the one described by the main clause, i.e. it locates the situation of the gerund clause before the one of the main clause. However, in Portuguese the compound form can also be associated with temporal relations of posteriority, overlapping and temporal underspecification (see Leal, 2001; Móia & Viotti, 2005; Lobo, 2006; Cunha et al., 2008 a.o.). This non-anteriority compound gerund exhibits certain peculiarities, namely (i) it can only occur to the right of the matrix clause, (ii) it can freely alternate with the simple gerund, without affecting the interpretation of the clause, and (iii) it can only co-occur with certain T heads in the matrix clause, namely with those containing an [+ ANTERIOR] feature. Wurmbrand (2012) describes a similar set of properties for the parasitic participles in Germanic languages and explains them through feature valuation in Reverse Agree. In this paper, I will argue that the Portuguese non-anteriority compound gerund is a product of the same syntactic mechanism and occurs due to feature valuation of the gerund T against the matrix T in Upward Agree.